(untitled) (Fiep Bulletin - online, 2014)
ABSTRACT: The control of the intensity in the aquatic environment, still today, is a question very argued by literature, due to physiology to be different in the exercises carried through in water and land. In the aquatic environment, reduction in heart rate occurs and formulas for the establishment of a target heart rate (HR) are not scientifically validated. Therefore, the objective of this study was to investigate answers of heart rate and perceived exertion in water exercises practitioners. The present research was classified as almost experimental of field in a exploratory concept. 10 women, apparently healthful had been selected for this research, with ages between 40 and 60 years, that at least had 3 months of practical. Using a heart rate monitor (Polar), the HR was verified with the individuals seated in a chair, after 5 minutes, for attainment of the value in rest; inside of water, the HR rest was surveyed 5 minutes of vertical immersion after, with depth of the water in the line of the xiphoid process. Also it was used scale of Borg of 15°. During the class, with total duration of 35 minutes, to each 5 minutes the HR of the individuals was verified and requested they who attributed a value to its effort. For treatment of the data, beyond the descriptive statistics, the test of Pearson was used, to correlate the 0 variable of the study, that had been to impose norms in accordance with the values gotten in the rest condition. The joined results had demonstrated a significant correlation (r=0,96) enter the values of HR and subjective exertion perception (SEP), with level of significance of p<0,01. Thus, it is concluded that the control of the intensity in water exercises classes through the effort perception is possible, practical method and of easy learning on the part of the practitioners. Research with individuals of the masculine sex, other ages and methods of training is recommended, for deepening on this subject.